Pancasila Paradigm: Methodology of Wawasan Nusantara for Accounting of Pancasila - Zulkarim Salampessy; Iwan Triyuwono; Gugus Irianto; Bambang Hariadi (Australasian Accounting, Business and Finance Journal, 2018)
The purpose of this paper is to present the research methodology of the accounting paradigm “Pancasila”. Pancasila is the basic view of life appropriate to the citizens of Indonesia's independence. In the paradigm of Pancasila, there are contained elements of philosophical research or basic beliefs that underlie accounting thought and research. These elements are based on the nature of Pancasila human beings, i.e. the first point of Pancasila, Ketuhanan Yang Maha Esa (The Almighty God) contains elements of life, as a study of ontology; the second point, Kemanusiaan yang Adil dan Beradab (Just and Civilized Humanity), contains elements of the senses, the mind, and rasa as the study of epistemology; the third point, Persatuan Indonesia (the Unity of Indonesia), contains elements of Karsa (will) in concepts of Wawasan Nusantara as the study methodology, i.e. the Methodology of Wawasan Nusantara (MWN); the fourth point, Kerakyatan yang dipimpin oleh Hikmah Kebijaksanaan dalam Permusyawaratan / Perwakilan (Democracy Guided by the Inner Wisdom in Deliberations and Representations), contains elements of deeds and inner wisdom as a method of research; and fifth points, Keadilan Sosial bagi Seluruh Rakyat Indonesia (Social Justice for all the People of Indonesia), contains elements of purpose as the study of axiology, namely the research results in the form of the concept and practice of accounting based on Pancasila.
Keywords: Pancasila; Paradigm; Accounting Research; Ontology; Epistemology; Methodology; Methods; Axiology.